2015
DOI: 10.1093/ejcts/ezv259
|View full text |Cite
|
Sign up to set email alerts
|

Aortic events after isolated aortic valve replacement for bicuspid aortic valve root phenotype: echocardiographic follow-up study

Abstract: Patients with a BAV root phenotype are at significant risk of aortic events after isolated AVR. Simultaneous root/ascending aortic surgery should be strongly considered in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…However, a persistent risk of dissection remains at the sinus of Valsalva level. According to some studies, the sinus of Valsalva continues to dilate even after aortic valve replacement surgery 6. The occurrence of aortic dissection in a patient operated on his aortic valve, without aortic dilatation, raises the problem of predicting the fragility of the aorta.…”
Section: Introductionmentioning
confidence: 99%
“…However, a persistent risk of dissection remains at the sinus of Valsalva level. According to some studies, the sinus of Valsalva continues to dilate even after aortic valve replacement surgery 6. The occurrence of aortic dissection in a patient operated on his aortic valve, without aortic dilatation, raises the problem of predicting the fragility of the aorta.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Wang et al (2016) found that patients with BAV-AI had a higher prevalence of R-L fusion phenotypes and wider aortic roots than patients with BAV-AS. Girdauskas et al (2015a) found that 34% of participants with BAV and root phenotype suffered aortic complications after AVR and only 50% of patients in the study were unburdened by aortic complications 15 years post-AVR. Girdauskas et al reported that 3/56 patients with root phenotype expired due to type A dissection, while 0/153 patients with stenosis and ascending aortic dilation suffered a Type A aortic dissection (Girdauskas et al, 2012, 2015a).…”
Section: Resultsmentioning
confidence: 79%
“…A study of 56 patients with pure AI, who had an isolated AVR found that the subset of patients with a root aneurysm and AI appears to be different than the hemodynamically-triggered aortopathy seen in patients with BAV stenosis and asymmetric dilation of the tubular ascending aorta (Girdauskas et al, 2015a). This root phenotype (root aneurysm and AI) of BAV has been linked to more of a genetic/aortopathy cause, and occurs earlier in life and independent of hemodynamic factors (Della Corte et al, 2007; Girdauskas et al, 2015a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an inconsistency might be at least partially explained by the heterogeneous nature of BAV disease that may become manifest in different types of aortopathy (ie, so-called BAV phenotypes). Based on our personal experience, those patients with BAV presenting with a regurgitation of BAV and root-type dilatation of the proximal aorta (so-called root phenotype) might have a severe congenitally triggered aortopathy and, therefore, may be of particular interest for an accelerated IA formation 8. These root-phenotype patients with BAV are very different in their presentation compared with those patients presenting with BAV stenosis and an eccentric dilatation of the tubular ascending aorta.…”
mentioning
confidence: 99%